Engineered Cytokine Signaling to Improve CAR T Cell Effector Function - Bell, Matthew; Gottschalk, Stephen (Frontiers in Immunology, 2021)
Adoptive immunotherapy with T cells genetically modified to express chimeric antigen receptors (CARs) is a promising approach to improve outcomes for cancer patients. While CAR T cell therapy is effective for hematological malignancies, there is a need to improve the efficacy of this therapeutic approach for patients with solid tumors and brain tumors. At present, several approaches are being pursued to improve the antitumor activity of CAR T cells including i) targeting multiple antigens, ii) improving T cell expansion/persistence, iii) enhancing homing to tumor sites, and iv) rendering CAR T cells resistant to the immunosuppressive tumor microenvironment (TME). Augmenting signal 3 of T cell activation by transgenic expression of cytokines or engineered cytokine receptors has emerged as a promising strategy since it not only improves CAR T cell expansion/persistence but also their ability to function in the immunosuppressive TME. In this review, we will provide an overview of cytokine biology and highlight genetic approaches that are actively being pursued to augment cytokine signaling in CAR T cells.